2017
DOI: 10.1507/endocrj.ej17-0026
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of thyroid cancer [Review]

Abstract: Abstract. Thyroid cancers have long been considered to arise in middle age and, after their repeated proliferation, resulting in further damage to the genome, they progress to more aggressive and lethal cancers. However, in 2014, some studies were reported that might lead to a marked change in our understanding of the natural history of thyroid cancer. A high prevalence of papillary carcinoma in the young suggested that the first initiation of thyroid cancer is likely to occur in the infantile period. Such a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 34 publications
(37 reference statements)
2
63
0
3
Order By: Relevance
“…19 Takano 20 offers an interesting theory about the natural history of thyroid cancer, and Japanese studies give evidence that PTC is a common childhood phenomenon. 21 Baseline US studies performed on children following the 2011 Fukushima nuclear plant accident revealed a prevalence of thyroid cancer of 37.3/100,000.…”
Section: Is Ptc a Common Childhood Phenomenon?mentioning
confidence: 99%
See 4 more Smart Citations
“…19 Takano 20 offers an interesting theory about the natural history of thyroid cancer, and Japanese studies give evidence that PTC is a common childhood phenomenon. 21 Baseline US studies performed on children following the 2011 Fukushima nuclear plant accident revealed a prevalence of thyroid cancer of 37.3/100,000.…”
Section: Is Ptc a Common Childhood Phenomenon?mentioning
confidence: 99%
“…21,22 Autopsy data from Japan have shown increasing prevalence of PTC from ages 15 through 34 years with no increase thereafter. 20 Papillary carcinoma may arise from thyroblasts, grow during childhood and early adulthood, then either regress, nonlethally progress, or persist as an indolent lesion in adulthood. Lethal thyroid tumors are rare, arise in older adults, and may be of a different origin.…”
Section: Is Ptc a Common Childhood Phenomenon?mentioning
confidence: 99%
See 3 more Smart Citations